FREQUENCY ANALYSIS OF PHOTOGRAPHIC OBSERVATIONS OF PULSATING STARS - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
The Fourier analysis are performed for photoelectric and photographic B-observations (Goranskij and Shugarov, 1979) of RR Lyrae star RW Ari. Besides the main frequency f0 and four its first harmonics two more frequencies are found: f1 =f0 /3 and f2 =0.711f0 c/d. It permits to identify frequencies: f0 as fs, introduced by us earlier (Bezdenezhnyi, 1997b) for RR Lyrae star T Sex, and f2 - as f1H. Such analysis of photographic author's observations of RR Lyrae star BK Dra is performed too. It is shown that BK Dra is a multiperiodic variable star. Its frequencies identifications are carried out and given. Three data sets of Cepheid V477 Oph: visual author's (Bezdenezhnyi and Mandel, 1977), photographic Mandel's (1970) observations and (O-C) - residuals (Hacke, 1988) show that V477 Oph apparently can be referred to bimodal Cepheids.